2021
DOI: 10.21203/rs.3.rs-198787/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opioid Use in Medical Cannabis Authorization Adult Patients from 2013-2018: Alberta, Canada

Abstract: Background: The opioid overdose epidemic in Canada and the United States has become a public health crisis - with exponential increases in opioid-related morbidity and mortality. Recently, there has been an increasing body of evidence focusing on the opioid-sparing effects of medical cannabis use (reduction of opioid use and reliance), and medical cannabis as a potential alternative treatment for chronic pain. The objective of this study is to assess the effect of medical cannabis authorization on opioid use (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…For example, pain was one of the highest conditions noted where medical cannabis is being used in this cohort of patients. We have previously shown that cannabis may have important impacts to help reduce the use of opioids for chronic pain at the population level [35]. Thus, medical cannabis authorization could be a potential strategy to minimize harm associated with opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pain was one of the highest conditions noted where medical cannabis is being used in this cohort of patients. We have previously shown that cannabis may have important impacts to help reduce the use of opioids for chronic pain at the population level [35]. Thus, medical cannabis authorization could be a potential strategy to minimize harm associated with opioid use.…”
Section: Discussionmentioning
confidence: 99%